Association Between Dietary Fiber Intake and Heart Failure Among Adults: National Health and Nutrition Examination Survey 2009–2018 - Zhang, Hao; Lin, Zhibin; Chen, Jun; Gan, Daojing; Zhou, Haobin; Ma, Zhuang; Zeng, Xianghui; Xue, Yuting; Wang, Xiao; Zhan, Qiong; Zeng, Qingchun; Xu, Dingli (Frontiers in Cardiovascular Medicine, 2022)
Objective: To explore the association between dietary fiber and heart failure (HF). Methods: Data were collected from the 2009–2018 National Health and Nutrition Examination Survey (NHANES). Dietary fiber intake data was obtained from two 24-h dietary recall interviews. Logistic regression and restricted cubic spline models were used to explore the association of dietary intakes of total, cereal, fruit, and vegetable fiber with HF prevalence. Results: A total of 21869 adults were included in this study. After adjusting for multiple confounding factors, the odds ratios (OR) and 95% confidence intervals (CI) for HF was 0.55 (0.32 to 0.95, P for trend= 0.011) for the highest tertile versus lowest tertile of total fiber intake. Similar results were observed for cereal but not fruit and vegetable fiber intake. Dose-response analysis indicated that dietary intake of total and cereal fiber were inversely associated with HF in a linear manner. Conclusion: Intakes of total and cereal fiber were inversely associated with HF in US adults.